Wang Shu’s promenade of strolling in shan-shui and its dialogue with Le Corbusier’s concept - Mingyue Zhang; Jin Baek (Journal of Asian Architecture and Building Engineering)
The architectural promenade, developed by Le Corbusier, is also a significant design concept in the contemporary architectural works of Wang Shu. This paper focused on Wang Shu’s and Le Corbusier’s promenade concepts aiming to illustrate how Wang’s promenade of strolling in Shan-shui establishes a cross-cultural dialogue with Le Corbusier’s theory. These two promenade approaches appear to have emerged from distinct historical and cultural contexts, with Le Corbusier’s approach rooted in Western modernism and Wang’s approach reflecting the aesthetics of traditional Chinese landscape painting. Seemingly unrelated, a thorough case analysis of Le Corbusier’s Villa La Roche and Wang’s Ningbo Tengtou Pavilion unveiled commonalities in creating picturesque spaces and spatial movement. Furthermore, both promenade approaches trigger discussions on architecture. Whereas Le Corbusier’s architectural promenade facilitated the creation of “new” architecture, Wang was inspired by Le Corbusier’s way of thinking, but aimed to “rebuild a kind of Chinese vernacular architecture” in response to the status quo of China’s urban architectural development. Wang Shu’s promenade opens a spectrum between traditional landscape painting and Le Corbusier’s ideas, showcasing a fusion of influences and inspirations from diverse cultural contexts, while also contributing to an understanding of the integration of Eastern and Western architecture in contemporary discourse.